A Database on Mycorrhizal Traits of Chinese Medicinal Plants - Zhang, Menghan; Shi, Zhaoyong; Zhang, Shan; Gao, Jiakai (Frontiers in Plant Science, 2022)
The mycorrhizal traits of plants have been widely reported based on different scales or plant functional groups. The mycorrhizal traits of medicinal plant have still been not studies systematically. Here a database on mycorrhizal traits including mycorrhizal type or status of Chinese medicinal plant species was assembled. In this study, the mycorrhizal type or status of a total of 3230 medicinal plants was presented. Among of them, mycorrhizal traits of 1321 species were ascertained. These medicinal plants had 3 mycorrhizal statuses, single mycorrhiza (SM) and multi-mycorrhiza (MM) contained 4 mycorrhizal types. The majority of medicinal plants were obligately symbiotic with mycorrhizal fungi with 926 (70.10%) species. Arbuscular mycorrhiza (AM) associated with 842 medicinal plant species (90.93% of obligately mycorrhizal), which was the most widespread mycorrhizal type. And ectomycorrhiza (ECM) was 15 species. This was the first exclusive database on mycorrhizal traits of medicinal plants, which provide both mycorrhizal type and status. This database provides valuable resources for identifying the mycorrhizal information of medicinal plants and enriching the theory of mycorrhizal traits which will be of great benefit to production or management of medicinal plants.